Exploration of Factor Structure and Measurement Invariance by Gender for a Modified Shortened Adapted Social Capital Assessment Tool in India - Hasan, Md Zabir; Leoutsakos, Jeannie-Marie; Story, William T.; Dean, Lorraine T.; Rao, Krishna D.; Gupta, Shivam (Frontiers in Psychology, 2019)
Social capital is defined as the nature of the social relationship between individuals or groups, and the embedded resources available through their social network. It is considered as a critical determinant of health and wellbeing. Thus, it is essential to assess the performance of any tool when meaningfully comparing social capital between specific groups. Using measurement invariance (MI) analysis, this paper explored the factor structure of the social capital of men and women measured by a modified Shortened Adapted Social Capital Assessment Tool (SASCAT-I) in rural Uttar Pradesh (UP), India. The study sample comprised 5,287 men (18-101 years) and 7,186 women (15-45 years), from 6,218 randomly selected households, who responded to SASCAT-I during a community-level cross-sectional survey. Social capital factor structure was examined by both exploratory and confirmatory factor analysis (CFA) and measurement invariance across gender was investigated using multi-group CFA. While disregarding gender, four unique factors (Organizational Participation, Social Support, Trust, and Social Cohesion) represented the structure of social capital. The MI analysis presented a partial metric-invariance indicating factor loadings for Organizational Participation, and Social Support were the same across gender. The gender-stratified analysis demonstrated a four-factor solution was best fitted for both men and women. Men and women of rural UP interpreted social capital differently as the perception of Trust and Social Cohesion varied across gender. For any future applications of SASCAT-I, we recommend gender-stratified factor analysis to quantify social capital's measure acknowledging its multidimensionality.